2015
DOI: 10.1111/tpj.13003
|View full text |Cite
|
Sign up to set email alerts
|

The wheat transcription factor TaGAMyb recruits histone acetyltransferase and activates the expression of a high‐molecular‐weight glutenin subunit gene

Abstract: SUMMARYGlutenin proteins in wheat (Triticum aestivum L.) flour confer unique viscoelastic properties to dough products and, therefore, the concentration and composition of the glutenin proteins determine its end-use value. However, the mechanisms governing the glutenin gene expression remain elusive. In this study, we report that wheat TaGAMyb activates the high-molecular-weight glutenin subunit genes (TaGLU) through recruiting the histone acetyltransferase GCN5. By sequencing the promoters of TaGLU-1 genes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 43 publications
1
54
0
Order By: Relevance
“…() identified TaFUSCA3, a B3 TF, which binds an RY motif in the GluB1‐1 promoter, activating the promoter and interacting with SPA protein. TaGamyb binds the AACA motif and activates the GluD1‐2 gene promoter in Arabidopsis (Guo et al ., ). Near the GLM‐GATA box, AACA and RY motifs were identified (Ravel et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…() identified TaFUSCA3, a B3 TF, which binds an RY motif in the GluB1‐1 promoter, activating the promoter and interacting with SPA protein. TaGamyb binds the AACA motif and activates the GluD1‐2 gene promoter in Arabidopsis (Guo et al ., ). Near the GLM‐GATA box, AACA and RY motifs were identified (Ravel et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…[30][31][32] In wheat, the number of wheat MYB TFBSs is correlated with the abundance of glutenin in different wheat cultivars. 15) In the present study, we predicted the TFBSs in the upstream regions of wheat fl-cDNA sequences using PWMs; the profiles of 14 TFBS types were analyzed with 54 PWMs. The Pvalue of the two-tailed test was 1.000, indicating that there were no significant differences among the average numbers of TFBSs per fl-cDNA for the 14 TFBS types ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…48) Moreover, Guo et al found that MYB TFs play an important role in the regulation of the glutenin gene expression during wheat endosperm development by directly binding to the promoter of TaGLU-1 and by recruiting GCN5 to modulate histone acetylation. 15) The plant B3 superfamily has two subfamilies, ARF and B3, and the B3 domain is the defining domain. 12) The B3 family is involved in flowering time control and in organ growth and polarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wheat, TaSPA, the O2-like bZIP factor, recognizes the GLM (GCN4-like motif) in the bi-factorial endosperm box to regulate expression of the low molecular weight glutenin subunit (LMW-GS) gene (Albani et al, 1997). TaGAMyb, which attaches to the R2R3MYB family, has been identified to interact with the histone acetyltransferase TaGCN5 to activate the expression of TaGLU-1Dy , a HMW-GS gene in wheat (Guo et al, 2015). Regulation of the expression of SSPs is accomplished by the integrated action of multitudinous TFs (Shekhar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%